Performance of Three Commercial Viral Load Assays, Versant Human Immunodeficiency Virus Type 1 (HIV-1) RNA bDNA v3.0, Cobas AmpliPrep/Cobas TaqMan HIV-1, and NucliSens HIV-1 EasyQ v1.2, Testing HIV-1 Non-B Subtypes and Recombinant Variants - Holguín, Africa; López, Marisa; Molinero, Mar; Soriano, Vincent (Journal of Clinical Microbiology, 2008)
Monitoring antiretroviral therapy requires that human immunodeficiency virus type 1 (HIV-1) viremia assays are applicable to all distinct variants. This study evaluates the performance of three commercial viral load assays--Versant HIV-1 RNA bDNA v3.0, Cobas AmpliPrep/Cobas TaqMan HIV-1, and NucliSens HIV-1 EasyQ v1.2--in testing 83 plasma specimens from patients carrying HIV-1 non-B subtypes and recombinants previously defined by phylogenetic analysis of the pol gene. All 28 specimens from patients under treatment presented viremia values below the detection limit with the three methods. In the remaining 55 specimens from naive individuals viremia could not be detected in 32.7, 20, and 14.6% using the NucliSens, Versant, or TaqMan tests, respectively, suggesting potential viral load underestimation of some samples by all techniques. Only 32 (58.2%) samples from naive subjects were quantified by the three methods; the NucliSens test provided the highest HIV RNA values (mean, 4.87 log copies/ml), and the Versant test provided the lowest (mean, 4.16 log copies/ml). Viremia differences of greater than 1 log were seen in 8 (14.5%) of 55 specimens, occurring in 10.9, 7.3, and 5.4%, respectively, of the specimens in comparisons of Versant versus NucliSens, Versant versus TaqMan, and TaqMan versus NucliSens. Differences greater than 0.5 log, considered significant for clinicians, occurred in 45.5, 27.3, and 29% when the same assays were compared. Some HIV-1 strains, such as subtype G and CRF02_AG, showed more discrepancies in distinct quantification methods than others. In summary, an adequate design of primers and probes is needed for optimal quantitation of plasma HIV-RNA in non-B subtypes. Our data emphasize the need to use the same method for monitoring patients on therapy and also the convenience of HIV-1 subtyping.